Music Inside Out: Going Too Far in Musical Essays - Rahn, John; Boretz, Benjamin (Routledge Amsterdam, 2000)
John Rahn's prolific activities as a composer-theorist-teacher, inventor of computer sound-synthesis software, editor of Perspectives of New Music during the 1980s and 90s, and author of an exemplary text on atonal theory are conspicuously in the foreground of the academic music-intellectual world. This collection of essays charts Rahn's progression from the construal of music's data structures to the articulation of its experiential structures, leading to the question of its moral infrastructures and its value systems of the internal and external worlds. This book shows Rahn's remarkable intellectual evolution, culminating in the recognition that the pressure bearing on discourse can only be contained by thought formulated in the non-referential language of the arts themselves.
Keywords: Music theory; Music criticism